The Structural Determinants of External Vulnerability - Loayza, Norman V.; Raddatz, Claudio (World Bank, Washington, DC, 2012)
The authors examine empirically how domestic structural characteristics related to openness and product- and factor-market flexibility influence the impact that terms-of-trade shocks can have on aggregate output. For this purpose, they apply an econometric methodology based on semi-structural vector auto-regressions to a panel of 90 countries with annual observations for the period 1974-2000. Using this methodology, the authors isolate and standardize the shocks, estimate their impact on GDP, and examine how this impact depends on the domestic conditions outlined above. They find that larger trade openness magnifies the output impact of external shocks, particularly the negative ones, while improvements in labor market flexibility and financial openness reduce their impact. Domestic financial depth has a more nuanced role in stabilizing the economy. It helps reduce the impact of external shocks particularly in environments of high exposure-that is, when trade and financial openness are high, firm entry is unrestricted, and labor markets are rigid.